2021
DOI: 10.3390/nu13061870
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simplified Creatinine Index and Systemic Inflammatory Markers for Nutritional Evaluation of Hemodialysis Patients

Abstract: Protein-energy wasting (PEW) is associated with adverse outcomes in hemodialysis patients. This study compares the simplified creatinine index (SCI) and circulating inflammatory markers as nutritional screening tools for hemodialysis patients. Maintenance hemodialysis patients (230 total patients, 34.8% women, 64.0 ± 14.3 years old) from a tertiary medical center were assessed for demographic data, body composition analysis, biochemistry tests, and circulating inflammatory biomarkers. The SCI was calculated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Both serum creatinine and albumin are known to be relevant clinical markers of nutritional state in HD patients [19], which is supported by the present findings of a significant and positive correlation between serum creatinine and albumin (r = 0.388, p < 0.0001). Furthermore, results showing that creatinine was significantly and inversely correlated with serum log CRP in the present cohort (r = −0.194, p = 0.0004) indicated that the serum FT3/FT4 ratio is significantly influenced by both nutrition and inflammation in HD patients, as previously described [20]. In multivariate models that included serum creatinine, albumin, and log CRP as independent variables, serum creatinine alone retained a significant and positive association with the serum FT3/FT4 ratio in each of those models (Models 4-7, Table 2), suggesting that the independent association of serum creatinine with the serum FT3/FT4 ratio is by a mechanism other than nutritional and inflammation factors.…”
Section: Discussionsupporting
confidence: 86%
“…Both serum creatinine and albumin are known to be relevant clinical markers of nutritional state in HD patients [19], which is supported by the present findings of a significant and positive correlation between serum creatinine and albumin (r = 0.388, p < 0.0001). Furthermore, results showing that creatinine was significantly and inversely correlated with serum log CRP in the present cohort (r = −0.194, p = 0.0004) indicated that the serum FT3/FT4 ratio is significantly influenced by both nutrition and inflammation in HD patients, as previously described [20]. In multivariate models that included serum creatinine, albumin, and log CRP as independent variables, serum creatinine alone retained a significant and positive association with the serum FT3/FT4 ratio in each of those models (Models 4-7, Table 2), suggesting that the independent association of serum creatinine with the serum FT3/FT4 ratio is by a mechanism other than nutritional and inflammation factors.…”
Section: Discussionsupporting
confidence: 86%
“…The mCI is an indicator of muscle wastage and an objective nutritional assessment tool used in HD patients [7,27,28]. Hwang et al reported that the mCI was correlated with the GNRI [12], and Tsai et al recently found that the mCI is an independent predictor of PEW [29]. Furthermore, some studies reported that the mCI is a useful tool to predict the occurrence of new cardiovascular events and that of infection-associated or all-cause mortality [11][12][13]30].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was separated within 30 min and stored at −80 °C for subsequent analyses. Then, the plasma levels of galectin-3, interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and monocyte chemoattractant protein-1 (MCP-1/CCL2) were detected using an inhouse multiplex bead-based immunoassay (MBIA) according to a published protocol [ 27 , 28 ]. Briefly, we added the samples and standard dilutions to 96-well microplates containing fluorescence-encoded microspheres precoated with analyte-capturing antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…When the patient’s DW exceeded the IBW, the DW/IBW ratio was set to 1. A GNRI score of ≤98 indicated a risk for malnutrition [ 27 , 31 ].…”
Section: Methodsmentioning
confidence: 99%